Pengaruh Model Pembelajaran Kooperatif Tipe NHT (Numbered Heads Together) Terhadap Hasil Belajar Siswa Kelas XI IPA SMA Negeri 1 Dolo Pada Materi Pelajaran Kimia Koloid - Febiliyanti, Rezha; Tiwow, Vanny M.A.; Gonggo, Siang Tandi (Universitas Tadulako, 2014)
This research is motivated by low achievement and lack of chemistry students in learning activities especially on the subject of colloids. Based on observations in SMA Negeri 1 Dolo, it has known that the process of teaching and learning suggests that teachers in teaching chemistry concepts and theories through learning activities centered on the teacher or just direct instruction, students were not actively engaged in activities and less opportunity to develop the students thinking process, so the learning process tends boring and turned to student learning laziness. These problems could be overcome by using a type of learning model NHT (Numbered Heads Together). This study aims to figure out the Effects of Cooperative Learning Model Type NHT (Numbered Heads Together) on Student Results of Class XI IPA SMAN I Dolo on topic Colloids. The population in this study was the students of class XI SMA Negeri 1 Dolo 2012/2013 school year, and the research sample was 33 students of class XI IPA 3 as the experimental class (learning by using NHT), and 34 students of class XI IPA 2 as a control class (direct learning). Data were obtained by providing post-test to both samples group. After that, the data were analyzed to test the hypothesis by using one tail t-test. The average and the deviation standard obtained for the experimental class was 64.15 and 10.75. While the average and deviation standard for control class was 53,03 and 10,21. Based on t-test analysis, it can be concluded that the learning outcomes of students who use cooperative learning model NHT (Numbered Heads Together) is higher than student learning outcomes using direct instructional model.